Decoding Urinary Tract Infection Trends: A 5-Year Snapshot from Central Portugal - Francisco Rodrigues; Patrícia Coelho; Sónia Mateus; Armando Caseiro; Hatem Eideh; Teresa Gonçalves; Miguel Castelo Branco (Clinics and Practice)
Introduction: This study analyzes urinary tract infections (UTIs) in a hospital in Central Portugal over a five-year period, focusing on bacterial prevalence, patient demographics, and antibiotic resistance patterns. This investigation aims to provide insights that can guide improved infection control and treatment strategies. Methods: A total of 6161 positive urine cultures collected over five years were examined, with particular emphasis on 2019 due to a peak in infection rates. The analysis explored bacterial prevalence, demographic factors such as sex and clinical service origin, and antibiotic resistance. Special attention was given to hospitalized patients, especially those undergoing invasive procedures, due to their increased vulnerability to infection. Results: This study found that UTIs were more prevalent in female patients, reflecting anatomical susceptibilities. Hospitalized individuals, particularly those requiring invasive procedures, were at greater risk. The predominant bacteria were Escherichia coli, Klebsiella pneumoniae, and Enterococcus faecalis, with differences in prevalence by patient sex and service origin. Resistance to Imipenem in E. coli increased, raising concerns about last-resort treatments. However, resistance to other antibiotics declined, suggesting improvements due to recent stewardship measures. During the COVID-19 pandemic, overall antibiotic consumption decreased due to changes in clinical practices. Conclusion: The findings highlight the importance of strict infection control, targeted prevention measures, and rational antibiotic use to combat resistance. Ongoing surveillance and personalized treatment approaches are essential to improve UTI management and outcomes.